2006
DOI: 10.1111/j.1365-2567.2006.02411.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cells of the B lineage in the human adult greater omentum

Abstract: Summary Peritoneal B cells and their omental precursors play an important role in the immune response of the peritoneal cavity and mucosal surfaces in mice. We have previously shown that peritoneal and mucosal B lineage cells are unlikely to be significantly linked in humans. However, the status of the omentum remains unknown. Here, using immunohistochemistry, we observed that sparse, quiescent B cells and occasional clusters of B cells were present in the omentum and that plasma cells, predominantly with cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…16,46 B-1 B cells may originate in the fatty omentum in the peritoneum of mice, 47 but again there is no evidence that the adult human omentum contains B cells that might either be precursors of or substitutes for B-1 B cells in the murine peritoneum. 48 There is a link between the murine spleen and the mucosa in this context. It has been recently shown that in mice, B-1a B cells and mucosal IgA derive from lineage-negative precursors found in the fetal liver that reside in the spleen after birth.…”
Section: Origin Of Iga Plasma Cellsmentioning
confidence: 98%
“…16,46 B-1 B cells may originate in the fatty omentum in the peritoneum of mice, 47 but again there is no evidence that the adult human omentum contains B cells that might either be precursors of or substitutes for B-1 B cells in the murine peritoneum. 48 There is a link between the murine spleen and the mucosa in this context. It has been recently shown that in mice, B-1a B cells and mucosal IgA derive from lineage-negative precursors found in the fetal liver that reside in the spleen after birth.…”
Section: Origin Of Iga Plasma Cellsmentioning
confidence: 98%
“…Use of the J1 segment of the heavy chain, for example, is seen in peripheral but not mucosal Bcell responses. 17 The VH1-46 segment is associated with the immune response to rotavirus, 18 and the VH5 family segments are associated with allergic disease. 19 We have used the criteria above to study B cells in the oral mucosa.…”
mentioning
confidence: 99%
“…Additionally, the use of certain gene segments can reflect selection into a particular functional repertoire. Use of the J1 segment of the heavy chain, for example, is seen in peripheral but not mucosal B‐cell responses 17. The VH1‐46 segment is associated with the immune response to rotavirus,18 and the VH5 family segments are associated with allergic disease 19.…”
mentioning
confidence: 99%